Radioguided thyroidectomy for follicular tumors: Multicentric experience. (May 2017) - Parmeggiani, D.; Gambardella, C.; Patrone, R.; Polistena, A.; De Falco, M.; Ruggiero, R.; Cirocchi, R.; Sanguinetti, A.; Cuccurullo, V.; Accardo, M.; Avenia, N.; Docimo, G.; et al.
Abstract: Background: The diagnosis of thyroid nodular diseases requires an integrated approach that has been widely established over the past years. This strategy includes: ultrasonography (US) with; implemented Color-Power-Doppler, conventional scintigraphy also with positive indicators, specific pathological studies targeted by immunohistochemically-assays, and the fine needle; aspiration biopsy (FNAB), which, usually, in case of "Follicular Lesions" (10–20%) findings is; unable to distinguish carcinoma from follicular adenoma, then indicating the necessity of surgery to; obtain a correct diagnosis. The aim of this study was to evaluate the role of the scintigraphy with; positive indicators, both preoperatively in diagnostic approach of the thyroid nodules and; intraoperatively as a guide to the extension of the surgical excision. Methods: On 4482 Thyroidectomy performed, we selected 360 cases of follicular neoplasms (192; females and 168 males). In the preoperative phase, these patients underwent 99 m Tc-sestaMIBI; scintigraphy with both early (10 min) and late (2 h) image acquisition, which were later; compared to the ones obtained by image subtraction of means 99 m Tc-pertechnetate. Following the; sestamibi administration before intervention, we selected the most up-taking nodularity with the; assistance of a specific surgical probe (Neoprobe), quantifying uptake with relation to the surgical pathology, for an amount of 324 total thyroidectomies and 36 hemi thyroidectomies. Results: In all cases of multinodular goiter the benign nodules showed an intraoperative low sestamibi uptake whereas follicular carcinomas showed both a high preoperative uptake and, as a; percentage, the highest values of intraoperative uptake; on the other hand, follicular adenomas had; both pre-and intraoperative mean values of uptake. On the contrary, papillary carcinomas only; showed a mild uptake. Conclusions: Preoperative sestamibi scintigraphy confirmed its importance in improving the information obtained through different diagnostic investigations. Also intraoperatively, it pointed; out high-risk nodules more accurately. Therefore, radio (Sestamibi) guided surgery could have an; interesting rule in the thyroid follicular lesion treatment. Highlights: The diagnosis of thyroid nodular diseases requires an integrated approach. In case of "Follicular Lesions" findings the non-invasive technique is unable to distinguish carcinoma from follicular adenoma, then indicating the necessity of surgery to obtain a correct diagnosis.